Research progress of keratin in oral squamous cell carcinoma - WANG Xiaohu; WANG Zuolin (Kouqiang hemian waike zazhi)
Keratin (KRT) is one of the members of the cytoskeletal protein intermediate filament family mainly distributed in the cytoplasm of epithelial cells, which plays a significant role in maintaining the morphology of epithelial cells and intercellular connections. In addition, KRT also participates in the occurrence and development of squamous cell carcinoma by regulating epithelial cell proliferation, migration, differentiation and epithelial-mesenchymal transformation (EMT). Oral squamous cell carcinoma (OSCC) is a common malignant tumor of the oral cavity which usually has a poor prognosis and low survival rate in patients. In recent years, the research on KRT in OSCC has gradually increased, and this paper expounds on the biological function of keratin and its research progress in OSCC.